Does Emotion Regulation Encourage PLWHA to Disclore Their Status? - - Rokhmah, Dewi; Nabila, Ichda Naila; Nafikadini, Iken (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: People living with HIV/AIDS (PLWHA) face numerous physical and psychological challenges that often lead to the emergence of negative emotional states. These emotional difficulties are frequently exacerbated by social stigma and discrimination, which can lead to diminished quality of life, decreased treatment adherence, and social withdrawal. Understanding how PLWHA manage their emotional responses is critical in developing supportive interventions. Objective: This study aims to analyze the factors that influence emotional regulation among PLWHA, with a focus on understanding the role of social and environmental support systems. By identifying key influences, the study seeks to inform strategies that foster better mental health outcomes in this vulnerable population. Methods: A qualitative case study approach was employed to obtain a deep understanding of the emotional experiences of PLWHA. Data were collected through in-depth interviews with 1 key informant, 8 PLWHA informants, and 5 additional informants including close family members and peers. Furthermore, Focused Group Discussions (FGDs) were conducted with 6 peer companions to enrich the data and validate individual findings. Thematic content analysis was used to identify recurring patterns and themes across the data. Result: Emotional regulation among PLWHA is significantly influenced by environmental acceptance and the availability of social support, particularly from family and peer companions. Positive social interactions contribute to increased motivation to pursue medical treatment and improve life satisfaction. On the other hand, ongoing stigma and discrimination were found to trigger negative emotional responses, including anxiety, shame, and social isolation. Conclusion: Emotional regulation in PLWHA is shaped by multiple interconnected factors, such as environmental support, traumatic past experiences, and physical changes associated with the illness. Interventions that focus on reducing societal stigma and enhancing the role of family and peer support are essential to promote resilience and positive emotional well-being among PLWHA.